Effect of generator configuration on the free-piston motion and power generation of air-driven expander system - A. Aziz, A.R. (Elsevier B.V., 2022)
The free-piston linear generator (FPLG) with a dual-piston air-driven system is a novel type of energy conversion device that converts mechanical energy into electric power through a linear generator. This paper investigates a novel FPLG utilising different generator stator core configurations (GA, GB, GC, GD, and GD) with an optimised valve opening control and the inlet pressure of 5 bar and 8 bar. The effect of generator configuration on the translator motion characteristics, root mean square (RMS) power output, as well as the system stability and the conversion efficiency, are duly discussed. The results show that the piston motion is affected by the generator configuration and the inlet pressure. The maximum RMS power achieved is 203.9 W when GB is used, whereas the maximum operating frequency of 13.8 Hz and a peak power output of 396 W are achieved when GD is used. The FPLG stability within the range for all generator configurations except for GA when the inlet pressure is 5 bar. The FPLG system conversion efficiency (thermal to work and work to electrical) is duly discussed. Â© 2021